Faktor-Faktor yang Berhubungan dengan Kejadian Unmet Need pada Pasangan Usia Subur di Desa Wangga Kecamatan Passi Barat Tahun 2023 - Lomban, Oktarizani; Desiyanti, Irne Wida; Ardiningtyas, Lisa (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the factors associated with the incidence of unmet need in couples of childbearing age in Wangga Village, Passi Barat District, Bolaang Mongondow Regency in 2023. This research method uses quantitative research and descriptive correlation design with a cross-sectional approach, namely conducting research at one time. The sampling technique in this study was Total sampling with a sample size of 68 respondents and data collection using a questionnaire sheet. The results showed that age (p-value 0.004 (<0.05), Education (p-value 0.004 (<0.05), Knowledge of KB (p-value 0.001 (<0.05), and husband's support p-value 0.001 (<0.05) are related to the occurrence of Unmet need. The results of the study found that there was a relationship between age factors, Education, knowledge of KB and husband's support with the occurrence of Unmet need. The results of the Mantel-Haenszel Common Odds Ratio Estimate Estimate showed that among several factors the most influential was husband's support with an odds ratio value of 3,500.